Integrating bioelectrochemical system with aerobic bioreactor for organics removal and caustic recovery from alkaline saline wastewater. - Weerasinghe Mohottige, Tharanga N; Ginige, Maneesha P; Kaksonen, Anna H; Sarukkalige, Ranjan; Cheng, Ka Yu (2023)
Bioelectrochemical systems (BES) are increasingly being explored as an auxiliary unit process to enhance conventional waste treatment processes. This study proposed and validated the application of a dual-chamber bioelectrochemical cell as an add-on unit for an aerobic bioreactor to facilitate reagent-free pH-correction, organics removal and caustic recovery from an alkaline and saline wastewater. The process was continuously fed (hydraulic retention time (HRT) of 6 h) with a saline (25 g NaCl/L) and alkaline (pH 13) influent containing oxalate (25 mM) and acetate (25 mM) as the target organic impurities present in alumina refinery wastewater. Results suggested that the BES concurrently removed the majority of the influent organics and reduced the pH to a suitable range (9-9.5) for the aerobic bioreactor to further remove the residual organics. Compared to the aerobic bioreactor, the BES enabled a faster removal of oxalate (242 ± 27 vs. 100 ± 9.5 mg/L.h), whereas similar removal rates (93 ± 16 vs. 114 ± 23 mg/L.h, respectively) were recorded for acetate. Increasing catholyte HRT from 6 to 24 h increased the caustic strength from 0.22% to 0.86%. The BES enabled caustic production at an electrical energy demand of 0.47 kWh/kg-caustic, which is a fraction (22%) of the electrical energy requirement for caustic production using conventional chlor-alkali processes. The proposed application of BES holds promise to improve environmental sustainability of industries in managing organic impurities in alkaline and saline waste streams.